First Record of Swallowtail Moth Epiplema fuscifrons (Warren,1896) (Uraniidae: Epipleminae) from Uttarakhand (Western Himalaya), India - Singh, Arun Pratap; Sahu, Lekhendra (Journal of the Bombay Natural History Society (JBNHS), 2024)
No Abstract.